Online travel UGC as persuasive communication: explore its informational and normative influence on pro-environmental personal norms and behaviour - Han, Wei (2018)
It is critical to motivate tourists to behave environmentally friendly for the sustainable development of tourism. The concept of pro-environmental tourist behaviour has been the subject of many research studies. However, only a few studies have focused on the effectiveness of using informational strategies to promote pro-environmental tourist behaviour, and these studies indicate that current strategies are not so effective in achieving behavioural change. Although it is widely accepted that personal norms are the dominant determinant of pro-environmental tourist behaviour, there have been limited studies in the tourism field related to activating pro-environmental personal norms. Therefore, this research topic needs to be enriched. The emergence of social media has drawn increasing research attention and its significance for tourism industry has been highlighted. Viewing social media as a channel of interpersonal influence, this research aims to investigate the influence of social media on pro-environmental tourist behaviour by activating personal norms. A conceptual model is built in this research to investigate the way people internalise travel user generated content (UGC) to salient pro-environmental personal norms. The influence of social media is viewed from the informational and normative aspects in the conceptual model. Adopting a mixed research design, this research conducted a study of netnography to understand the research topic and build the measurements for survey research in the second phase. The data about 140 most frequently read Chinese travel blogs confirms that it is possible to use social media as a channel to provide rich environmental information by public participation and collaboration. 1787 sample observations were used to test the relationship developed in the conceptual framework. After validating the developed scales by factor analysis, both the measurements and structural models were tested using a structural equation model (SEM) with partial least square approach (PLS-SEM). The results generally confirm the original conceptualisations. Both the informational and normative influence of social media positively impacts the activation of pro-environmental personal norms. The hypotheses on the moderating effects of prior knowledge and social media engagement are partially supported. The results indicate that social media is an effective tool in promoting pro-environmental tourist behaviour by activating personal norms. Findings of this research may be of interest to social marketers and environmental activists who intend to be opinion leaders. This study also is helpful for the relevant Chinese government institutions in working out effective information to encourage sustainable tourism since they have a huge control over the Chinese internet. Meanwhile, Chinese travel website managers who want to contribute to sustainable tourist behaviour promotion may also use the findings of this research.